(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The present paper is an attempt to investigate how phonology plays an important role in givingthat extra edge to the text. The author uses sound mechanism to make the reader hear what is happening.There is deliberate arrangement of phonemes, sound patterns, preference of certain specific consonantsover others to suit the context.